Targeting Akt and Heat Shock Protein 90 Produces Synergistic Multiple Myeloma Cell Cytotoxicity in the Bone Marrow Microenvironment - Alissa Huston; Xavier Leleu; Xiaoying Jia; Anne-Sophie Moreau; Hai T. Ngo; Judith Runnels; Judy Anderson; Yazan Alsayed; Aldo M. Roccaro; Sonia Vallet; Evdoxia Hatjiharissi; Yu-Tsu Tai; et al. (2008)
Abstract Purpose: We hypothesized that targeting both Akt and heat shock protein (HSP) 90 would induce cytotoxic activity against multiple myeloma (MM) cells and target the bone marrow (BM) microenvironment to inhibit angiogenesis, osteoclast formation, as well as migration and adhesion of MM cells. Experimental Design: MM cell lines were incubated with perifosine (5 and 10 μmol/L) and 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (17-DMAG; 50 and 100 nmol/L) alone and in combination. Results: The combination of Akt inhibitor perifosine and HSP90 inhibitor 17-DMAG was synergistic in inducing MM cell cytotoxicity, evidenced by inhibition of DNA synthesis and induction of apoptosis. In addition, perifosine and 17-DMAG almost completely inhibited osteoclast formation: perifosine interfered with both early and late stages of osteoclast progenitor development, whereas 17-DMAG targeted only early stages. We next showed that combined therapy overcomes tumor growth and resistance induced by BM stromal cells and endothelial cells as well as the proliferative effect of exogenous interleukin-6, insulin-like growth factor-I, and vascular endothelial growth factor. Moreover, the combination also induced apoptosis and growth inhibition in endothelial cells and inhibited angiogenesis. Finally, we showed that the two agents prevented migration of MM cells toward stromal-derived factor-1 and vascular endothelial growth factor, which are present in the BM milieu, and also prevented adhesion of MM cells to fibronectin. Conclusions: This study provides the preclinical framework for treatment protocols targeting both the Akt and HSP pathways in MM.